2006
DOI: 10.1080/10428190600572673
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte count as a predictor of death during remission induction in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) presenting with a high leukocyte count has been associated with an increase in induction mortality and poor results in a number of other survival measures. However, the level at which an elevated leukocyte count has prognostic significance in AML remains unclear. In this report on a series of 375 adult (non-M3) AML patients undergoing induction chemotherapy at a single institution, leukocyte count analyzed as a continuous variable is shown to be a better predictor of induction deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
3
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 26 publications
9
56
3
3
Order By: Relevance
“…About 10% of our patients had more than 100 9 10 9 L -1 at diagnosis, which is similar to the reported in developed countries [1,20,21]. In this study, we showed that hyperleukocytosis (here considered WBC [ 50 9 10 9 L -1 ) is an important predictive factor of ED in AML, even considering the finding that OS at our institution is poorer than previously reported by others [1,2]. This poor outcome can probably be explained by the inferior support infrastructure available for our patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…About 10% of our patients had more than 100 9 10 9 L -1 at diagnosis, which is similar to the reported in developed countries [1,20,21]. In this study, we showed that hyperleukocytosis (here considered WBC [ 50 9 10 9 L -1 ) is an important predictive factor of ED in AML, even considering the finding that OS at our institution is poorer than previously reported by others [1,2]. This poor outcome can probably be explained by the inferior support infrastructure available for our patients.…”
Section: Discussionsupporting
confidence: 89%
“…Hyperleukocytosis, conventionally defined as blast count superior to 50-100 9 10 9 L -1 in peripheral blood (PB), has been associated with an unfavorable prognosis due to early death and a higher risk of relapse [1,2]. Although the mechanisms of hyperleukocytosis are poorly understood, it was demonstrated that the malignant blasts are capable of adhering to the vascular endothelium and transmigrate into tissues [3][4][5], a condition called leukostasis syndrome (LS), which leads to the occlusion of small arteries in the brain, lungs and other organs by aggregates of blast cells and by blast cell thrombi, which causes hemorrhage, respiratory failure and higher relapse rate in the central nervous systems (CNS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellularity at diagnosis represents one of the important prognostic factors for AMLs [27]. The mean white blood cell (WBC) count in the whole population of leukemic patients here investigated was 83.…”
Section: Tie-2 ؉ Amls Display a High Cellularity At Diagnosismentioning
confidence: 99%
“…4,6,7 Patients with acute leukemia who present with hyperleukocytosis and symptoms of leukostasis have a poor prognosis, with mortality primarily due to intracranial hemorrhage and respiratory failure. [8][9][10] This appears to be especially true with AML, in which symptoms of leukostasis can manifest in patients with WBC counts as low as 50 ϫ 10 9 /L. The incidence of leukostasis is less in chronic myelogenous leukemia (CML) and chronic lymphocytic leukemia (CLL), perhaps in part due to the nature of the malignant cells.…”
Section: Hyperleukocytosis and Leukostasismentioning
confidence: 99%